The Effect of Murottal Intervention in Prolactine Hormone Levels of Breastfeeding Mothers in Takalar Regency - Syamsuriyati ,; Tahir Abdullah ,; Burhanuddin Bahar ,; Andi Indahwaty ,; Veni Haju ,; Ridwan Amiruddin ,; Toto Sudargo ,; Asry Dwi Muqni ,; Syamsuar Manyullei, (Journal of Pharmacy and Nutrition Sciences, 2019)
Breast milk is important for the infant’s growth and development early in life. Attention to lactating mothers in terms of increasing their breastmilk production is important. This study aimed to investigate the effect of giving murottal therapy on the levels of the hormone prolactin in lactating mothers in Takalar District. This was a true-experimental study in which 44 lactating mothers were divided into two groups, 22 mothers in intervention and 22 in control groups. The study was conducted in Takalar Regency, South Sulawesi Province, Indonesia. The characteristic of the participants showed that the age of participants in the intervention group is two years higher than in the control group. The number of mothers having more than three children is higher compared to the control (31.8% vs 9.1%). All characteristics of intervention and control were statistically not different. The result of this study showed that prolactin hormone levels were decreased in both groups. The prolactin hormone levels in the intervention group showed a lower decrease compared to control group (-89.84 ± 54.14 vs -103.54 ± 65.67), but not significantly different (p=0.453). The Qur’an therapy may be effective to replace music therapy to support lactation period and exclusive breastfeeding program, especially for those from Muslim communities. The District Health Office of Takalar can promote this therapy to improve lactation management program.